Corporate Social Responsibility Reporting in China: Symbol or Substance? - Marquis, Christopher; Qian, Cuili (Organization Science, 2014)
This study focuses on how and why firms strategically respond to government signals on appropriate corporate activity. We integrate institutional theory with research on corporate political strategy to develop a political dependence model that explains (a) how different types of dependency on the government lead firms to issue corporate social responsibility (CSR) reports and (b) how the risk of governmental monitoring affects the extent to which CSR reports are symbolic or substantive. First, we examine how firm characteristics reflecting dependence on the government—including private versus state ownership, executives serving on political councils, political legacy, and financial resources—affect the likelihood of firms issuing CSR reports. Second, we focus on the symbolic nature of CSR reporting and how variance in the risk of government monitoring through channels such as bureaucratic embeddedness and regional government institutional development influences the extent to which CSR communications are symbolically decoupled from substantive CSR activities. Our database includes all CSR reports issued by the approximately 1,600 publicly listed Chinese firms between 2006 and 2009. Our hypotheses are generally supported. The political perspective we develop contributes to organizational theory by showing that (a) government signaling is an important mechanism of political influence, (b) different types of dependency on the government expose firms to different types of legitimacy pressure, and (c) firms face a decoupling risk that makes them more likely to enact substantive CSR actions in situations in which they are likely to be monitored.